2021
DOI: 10.2340/00015555-3795
|View full text |Cite
|
Sign up to set email alerts
|

Anaemia in Dermatitis Herpetiformis: Prevalence and Associated Factors at Diagnosis and One-year Follow-up

Abstract: Dermatitis herpetiformis is a cutaneous manifestation of coeliac disease. Anaemia is a common finding in patients with untreated coeliac disease, but little is known about the occurrence of anaemia in those with dermatitis herpetiformis. This study investigated the prevalence of anaemia and factors associated with anaemia in 250 patients with dermatitis herpetiformis, at diagnosis and one year after diagnosis. As controls, 139 patients with coeliac disease were included. Patient records were reviewed to gather… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
0
1
0
1
Order By: Relevance
“…There have been only a few studies addressing the differences between males and females affected by DH, and the main focus has been on newly diagnosed patients. Previous studies have linked male sex with younger age at the onset of DH symptoms, more severe skin symptoms at diagnosis and more frequent initiation of dapsone after diagnosis ( 28 30 ). Furthermore, 2 studies have shown an increased risk for delayed diagnosis in females ( 21 , 29 ), but, in contrast, 1 study associated increased diagnostic delay with male sex ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…There have been only a few studies addressing the differences between males and females affected by DH, and the main focus has been on newly diagnosed patients. Previous studies have linked male sex with younger age at the onset of DH symptoms, more severe skin symptoms at diagnosis and more frequent initiation of dapsone after diagnosis ( 28 30 ). Furthermore, 2 studies have shown an increased risk for delayed diagnosis in females ( 21 , 29 ), but, in contrast, 1 study associated increased diagnostic delay with male sex ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…Hämolytische Anämie tritt bei allen Personen bis zu einem gewissen Grad auf. Eine Studie aus dem Jahr 2021, die die Prävalenz von Anämie bei DH untersuchte, ergab, dass die Anämie bei DH zwar relativ gering ist, aber häufiger auftritt, wenn der Patient Dapson verwendet [72]. Methämoglobinämie tritt auf, wenn rote Blutkörperchen Methämoglobin in Konzentrationen von mehr als 1% enthalten.…”
Section: Managementunclassified